L'enseignement scientifique, entre émancipation et asservissement ? - Denise Orange-Ravachol (Nantes Université, 2018)
French institutional texts on science education are now strongly focused on students' problem-based learning and take into account their investigations. Given this development it seems particularly interesting to study what happens during debates where students' explanatory ideas are expressed and confronted and during subsequent discussions, when the teacher aims at leading the class towards a reasoned and scientifically acceptable explanation. This is what we have sought to accomplish in this study, which is based on two « forced sequences » (body movements, volcanism, 9-11year-old students). We attempt to identify how this situation allows for the emancipation and the scientific acculturation of students. We show that the debates can allow each student to open up to other possible explanations, and thus to free himself/herself from his/her own production while bringing it into a common pool of ideas (acculturation/emancipation). But this movement towards emancipation is not immediate because students can confine themselves to their prejudices. Didactic devices such as caricatures of the different explanatory models of the class or classification of arguments, appear to be facilitators of both emancipation and acculturation.